Three-dimensional discrete element modelling of influence factors of indirect tensile strength of asphalt mixtures. Issue Volume 20:Issued 6(2019) (3rd June 2019) - Peng, Yong; Wan, Lei; Sun, Li-Jun
ABSTRACT: The purpose of this study is to investigate the effects of aggregate gradation, asphalt content and loading velocity on the indirect tensile test (IDT) strength of asphalt mixtures using three-dimensional discrete element method (DEM). A microstructure-based cohesive zone discrete element model for predicting the IDT strength at 20 °C was established by a discrete element program called Particle Flow Code in Three Dimensions. Based on this model, the effects of aggregate gradation, asphalt content and loading velocity on the IDT strength were numerically simulated. The simulation results were verified by performing an actual IDT test. Results reveal that the IDT test at 20 °C can be simulated well based on the cohesive zone DEM. Furthermore, the IDT strength of asphalt mixtures is remarkably affected by the aggregate gradation, asphalt content and loading velocity.